Legal regulation of environmental safety Kazakhstan and China. (Journal of actual problems of jurisprudence, 2016)
The article discusses some aspects of the development of environmental policy in Kazakhstan and China. The author analyzes the legislation of the two countries in the field of environmental protection. In addressing global environmental problems it addresses issues of international cooperation between the two states. Environmental security of the two countries , the terms of the political, economic and social security of the states do not always meet standards. Legislative measures taken by Kazakhstan and China to address environmental problems, are correct, but not always implemented in action.
Keywords: environmental safety; environment; environmental legislation